Analysis of Physiological Responses of Double and Single Pickleball Players Over the Age of 40 - Adiputra Wijaksana; Agus Rusdiana; Iwa Ikhwan Hidayat (Journal of Physical Education Health and Sport, 2026)
The sport of pickleball is increasingly popular in the adult age group, including those over 40 years of age, but studies of physiological responses and game characteristics, especially comparisons between singles and doubles, are still limited. This study aimed to analyze differences in physiological responses and game characteristics between singles and doubles games in pickleball players over the age of 40. This study used a cross-sectional design with participants who were selected as members of the GMPP Pickleball club using the purposive sampling technique. Physiological responses were measured through pulse rate (5 minutes, average, and maximum), while game characteristics included steps per minute, total steps, game duration, rally time, rest time between rallies, and number of strokes. Data were collected using a Polar clock device and direct observation during the game, then analyzed using descriptive statistics and an Independent Sample t-test with a significance level of 0.05. The results showed that there was no significant difference in all physiological variables between singles and doubles (p > 0.05). However, there were significant differences in the characteristics of the game, namely rally time, game duration, rest time between rallies, and total steps (p < 0.05), where doubles games had a higher duration and total activity than singles. Meanwhile, no significant differences were found in steps per minute and number of strokes. It can be concluded that the difference in the form of play does not affect the physiological response of players, but does affect the activity patterns and characteristics of the game. These findings show that singles and doubles games have different activity demands, even though they are at the same level of physiological intensity, so that both can be used as a form of physical activity for players over 40 years of age according to the purpose of training.